Relative impacts of climate change and land cover change on streamflow using SWAT in the Clackamas River Watershed, USA - Junjie Chen (IWA Publishing, 2021)
To understand the spatial–temporal pattern of climate and land cover (CLC) change effects on hydrology, we used three land cover change (LCC) coupled scenarios to estimate the changes in streamflow metrics in the Clackamas River Watershed in Oregon for the 2050s (2040–2069) and the 2080s (2070–2099). Coupled scenarios, which were split into individual and combined simulations such as climate change (CC), LCC, CLC change, and daily streamflow were simulated in the Soil and Water Assessment Tool. The interannual variability of streamflow was higher in the lower urbanized area than the upper forested region. The watershed runoff was projected to be more sensitive to CC than LCC. Under the CLC scenario, the top 10% peak flow and the 7-day low flow are expected to increase (2–19%) and decrease (+9 to −20 cm s), respectively, in both future periods. The center timing of runoff in the year is projected to shift 2–3 weeks earlier in response to warming temperature and more winter precipitation falling as rain. High streamflow variability in our findings suggests that uncertainties can stem from both climate models and hydrologic model parameters, calling for more adaptive water resource management in the watershed. HIGHLIGHTS Tightly coupled CLC change scenarios were used to model flow in the Soil and Water Assessment Tool.; Snow-influenced, forested watershed is more sensitive to CC than LCC.; Hydrologic variability is higher in the urban, agricultural part than the forested part.; Top 10% flow is projected to increase, while low flow is projected to decline.; Warming will shift the center timing of flow volume earlier from mid-May to late-April.;